Prevalence of extracranial carotid atherosclerosis in the patients with coronary artery disease in a tertiary hospital in Malaysia - Sahadevan, Mahavishnu; Chee, Kok Han; Tai, Mei Ling Sharon (Lippincott, Williams & Wilkins, 2019)
There is limited information regarding the prevalence of extracranial carotid atherosclerosis in the patients with coronary artery disease (CAD) undergoing coronary artery bypass graft (CABG) surgery in South East Asia. The primary objective was to assess the prevalence of extracranial carotid stenosis, raised carotid intima media thickness (CIMT), and plaques in the patients with CAD undergoing elective CABG. The secondary objective was to evaluate the risk factors for extracranial carotid atherosclerosis.A total of 119 consecutive patients with CAD undergoing elective CABG in a tertiary hospital in Malaysia were recruited. Data on the demographic characteristics and risk factors were collected. The ultrasound carotid Doppler findings comprising of raised CIMT, plaques, and stenosis in the extracranial carotid vessels were recorded.The mean age of the patients was 64.26 ± 10.12 (range 42-89). Most of the patients were men (73.1%). The patients consisted of 44 (37%) Malays, 26 (21.8%) Chinese, and 49 (41.2%) Indians.A total of 67 (56.3%) patients had raised CIMT, 89 (74.8%) patients had plaques, and 10 (8.4%) patients had stenosis in the internal and common carotid arteries. The mean age of patients with plaques was higher compared to those without plaques (66.00 ± 9.63 vs 59.10 ± 9.92, P = .001). The body mass index (BMI) of patients with stenosis was higher compared to those without stenosis (28.35 ± 4.92 vs 25.75 ± 3.16, P = .02).The patients with plaques were more likely to be older, whereas the patients with carotid stenosis were more likely to have higher BMI.